The Relationship Between Humeral Torsion and Arm Injury in Baseball Players: A Systematic Review and Meta-analysis. (March 2020) - Helmkamp, Joshua K.; Bullock, Garrett S.; Rao, Allison; Shanley, Ellen; Thigpen, Charles; Garrigues, Grant E.
Context: Humeral torsion (HT) has been linked to various injuries and benefits. However, the exact interplay between HT, shoulder range of motion (ROM), competition level differences, and injury risk is unclear. Objective: To determine the relationship between HT, ROM, and injury risk in baseball players. Secondarily, to determine HT based on competition level. Data Sources: PubMed, Embase, Web of Science, CINAHL, and Cochrane databases were searched from inception until November 4, 2018. Study Selection: Inclusion criteria consisted of (1) HT measurements and (2) arm injury or shoulder ROM. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: Two reviewers recorded patient demographics, competition level, HT, shoulder ROM, and injury data. Results: A total of 32 studies were included. There was no difference between baseball players with shoulder and elbow injuries and noninjured players (side-to-side HT difference: mean difference [MD], 1.75 [95% CI, –1.83 to 2.18]; dominant arm: MD, 0.17 [95% CI, –1.83 to 2.18]). Meta-regression determined that for every 1° increase in shoulder internal rotation (IR), there was a subsequent increase of 0.65° in HT (95% CI, 0.28 to 1.02). HT did not explain external rotation (ER ROM: 0.19 [95% CI, –0.24 to 0.61]) or horizontal adduction (HA ROM: 0.18 [95% CI, –0.46 to 0.82]). There were no differences between HT at the high school, college, or professional levels. Conclusion: No relationship was found between HT and injury risk. However, HT explained 65% of IR ROM but did not explain ER ROM or HA ROM. There were no differences in HT pertaining to competition level. The majority of IR may be nonmodifiable. Treatment to restore and maintain clinical IR may be important, especially in players with naturally greater torsion. HT adaptation may occur prior to high school, which can assist in decisions regarding adolescent baseball participation.